Optimal operation of oil and gas production using simple feedback control structures. (October 2019) - Krishnamoorthy, Dinesh; Fjalestad, Kjetil; Skogestad, Sigurd
Abstract: The purpose of this paper is to describe the control challenges related to optimal operation of oil and gas production wells, and show that optimal operation can be achieved using simple feedback control structures. In particular, we find that conventional feedback control structures can efficiently handle changes in active constraint regions using simple logics such as split-range and selectors. This eliminates the need for complex models to be used in the optimization problem, and in addition eliminates the need to solve numerical optimization problems online. Thus, by using only simple feedback controllers that have been used widely in the oil and gas industry, it has a higher chance of implementation. We demonstrate the use of simple feedback controllers on two application examples; 1) a gas-lift optimization simulation study with a network of six gas-lifted wells, 2) an experimental study of optimal control of electrical submersible pump (ESP) lifted oil wells tested on a large-scale experimental test facility with a full scale ESP and live viscous crude oil.